Responses from one session of Mat Pilates on anxiety indicators in apparently healthy women and breast cancer survivors - Oliveira, Ellen Gomes de; Marques, Vitor Alves; Damasio, Nathan Muci Aguiar; Silva, Anderson Garcia; Maciel, Vitor Andrade; Noleto, Flavia Batista Gomes; Rodarte, Tatiane Nunes da Silva; Vieira, Carlos Alexandre (Mastology, 2026)
Objective: To compare the responses of one Mat Pilates session on state anxiety indicators among women who survived breast cancer with apparently healthy women. Methods: Thirty women participated in the study, separated into a group of breast cancer survivors (BCS) (n=15; age 61.00 standard deviation ±8.60) and a group of apparently healthy women (n=15; age 59.07±6.78). The study was approved by the ethics committee of the Federal University of Goiás. State anxiety levels were evaluated by the IDATE, which consists of 20 statements in which volunteers must indicate how they feel at a given moment; the scores can range from 20–80, where: 20–34 represents mild or low anxiety; 35–49 moderate anxiety; 50–64 high or severe anxiety; and 65–80 very high anxiety or panic. The inclusion criteria for both groups were being in menopause and not participating in any regular resistance exercise program in the last six months. For the BCS group, the inclusion criteria were having undergone mastectomy or breast quadrantectomy and not having metastasized. The mean and standard deviation were used for data analysis. Results: There was no difference in the classification of anxiety levels between BCS and apparently healthy women, respectively (BCS pre-test: 34.00±7.07 and post-test: 34.00±6.78; healthy women pre-test: 30.00±6.68 and post-test: 31.00±4.77). Conclusion: The current results suggest no difference in the classification of anxiety levels between breast cancer survivors and women apparently healthy, although the classification of anxiety levels of both groups represents mild or low anxiety.